2021
DOI: 10.3389/fonc.2021.671354
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Based on T2-Weighted Imaging and Apparent Diffusion Coefficient Images for Preoperative Evaluation of Lymph Node Metastasis in Rectal Cancer Patients

Abstract: PurposeTo develop and validate a radiomics nomogram based on T2-weighted imaging (T2WI) and apparent diffusion coefficient (ADC) features for the preoperative prediction of lymph node (LN) metastasis in rectal cancer patients.Materials and MethodsOne hundred and sixty-two patients with rectal cancer confirmed by pathology were retrospectively analyzed, who underwent T2WI and DWI sequences. The data sets were divided into training (n = 97) and validation (n = 65) cohorts. For each case, a total of 2,752 radiomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
(78 reference statements)
1
16
1
Order By: Relevance
“…This study confirmed that "MaximumProbability", "MaximumProbability" and "MaximumProbability" were the most meaningful among all the GLCM features, showing differences in the regional signal intensity distribution, gray level skewness, uniformity and linear dependency within PDAC tissues with LNM or nLNM tendency (47). The value of some of the wavelet features we obtained has also been confirmed in recent studies on LNM of rectal cancer and cervical cancer, especially the features based on T2WI (21,24,48). We also found that only six features from T2WI were retained-fewer than those retained from PVP (eight features).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study confirmed that "MaximumProbability", "MaximumProbability" and "MaximumProbability" were the most meaningful among all the GLCM features, showing differences in the regional signal intensity distribution, gray level skewness, uniformity and linear dependency within PDAC tissues with LNM or nLNM tendency (47). The value of some of the wavelet features we obtained has also been confirmed in recent studies on LNM of rectal cancer and cervical cancer, especially the features based on T2WI (21,24,48). We also found that only six features from T2WI were retained-fewer than those retained from PVP (eight features).…”
Section: Discussionsupporting
confidence: 86%
“…T2-weighted imaging (T2WI) and the dynamic enhanced portal venous phase (PVP) of MRI can better depict the biological characteristics of pancreatic lesions and have therefore been applied to radiomics studies of pancreatic cancer (18)(19)(20), including for differential diagnosis, prognosis evaluations, and treatment response predictions. Although studies have shown that radiomics can be used for the preoperative prediction of LNM of malignant tumors (21)(22)(23)(24), few radiomics studies based on MRI image texture analysis have been conducted for the preoperative prediction of LNM of PDAC. Therefore, this study aimed to explore whether the use of T2WI and PVP features was feasible for predicting LNM of PDAC.…”
mentioning
confidence: 99%
“…Conversely, benign tumors have relatively low cell density and a large tissue gap, so the free diffusion movement of water molecules is relatively free, manifested by a high apparent diffusion coefficient. The apparent diffusion coefficient has been confirmed to have high value in identifying various malignant tumors (16)(17)(18)(19). Zheng et al found that the apparent diffusion coefficient had a high predictive value for the response to chemotherapy in gastrointestinal cancer patients with liver metastases (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although the D* and f values of IVIM‐DWI performed well in assessing the N‐LNM of primary lesion of rectal adenocarcinoma, the diagnostic efficiency was not enough high in the study. Recently, a prior study demonstrated that the radiomics nomogram, incorporating Rads‐score based on features from the T 2 WI and ADC images, has potential for the preoperative identification of LN status in patients with rectal cancer 26 . Perhaps, it is because DWI with ADC is a functional MRI sequence that can reflect the varying cellularity within a tumor, 27 the AUCs of ADC images were higher than the AUCs of T 2 WI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a prior study demonstrated that the radiomics nomogram, incorporating Rads-score based on features from the T 2 WI and ADC images, has potential for the preoperative identification of LN status in patients with rectal cancer. 26 Perhaps, it is because DWI with ADC is a functional MRI sequence that can reflect the varying cellularity within a tumor, 27 the AUCs of ADC images were higher than the AUCs of T 2 WI. Liu et al constructed a radiomics model based on VOIs of T 2 WI and DWI (b = 1000 sec/mm 2 ), which also achieved good diagnostic performance in the validation cohort.…”
Section: Discussionmentioning
confidence: 99%